Peran Notaris Dalam Pelaksanaan Hapusnya Perikatan Dengan Cara Penawaran Pembayaran Tunai Diikuti Dengan Penitipan Dan Penyimpanan - Syadzwina Hindun Nabila (PAMALI: Pattimura Magister Law Review, 2023)
Introduction: Duties and authorities of a Notary in carrying out the service function and achieving legal certainty in providing services to the public apart from making authentic deeds, the notary also has other authorities, one of which is acting as an intermediary in the settlement of the cancellation of an agreement in the form of offering cash payments followed by safekeeping and safekeeping.Purposes of the Research: The purpose of this study is to examine the role of a notary in settling the abolition of an agreement by offering a cash payment followed by safekeeping and safekeepingMethods of the Research: This research was conducted in a normative juridical manner, using bibliographical data as secondary data to examine the rules and norms in law.Results of the Research: The results of the research show that the Notary is appointed by law in terms of completing the cancellation of the agreement in the form of offering cash payments followed by safekeeping and safekeeping because a public official is required and is related to making authentic deeds as strong evidence as the existence of a legal certainty and justice.